Analisis Persepsi Penonton Tentang Fenomena Mistis Dalam Film Badarawuhi di Desa Penari - Nai, Maria Chandrayani Bai; Zahra, Putri Patimatul; Saharani, Shakila Mahsa (CV. ITTC INDONESIA, 2024)
In this research, the researcher investigates how the audience understands and interprets aspects of mystical phenomena contained in the movie